Proses Berpikir Aljabar Berdasarkan Level Kognitif Mahasiswa - Arie Purwa Kusuma; Nurina Kurniasari Rahmawati; Arfatin Nurrahmah (Institut Agama Islam Negeri Curup, 2023)
Algebraic thinking skills need to be developed through learning mathematics, this is necessary to improve understanding of algebraic concepts. The ability to generalize experiences about numbers and calculations is a component of algebraic thinking abilities. It is important to know the student's algebraic thinking process. By knowing the student's thinking process, you can find out where the student's difficulties are and the causes of these difficulties. This research aims to analyze students' algebraic thinking processes based on students' cognitive levels. This research is qualitative research with an exploratory method. The subjects of this research were 21 Semester II Mathematics Education students at STKIP Kusuma Negara Jakarta. The data collection technique begins with giving algebraic thinking questions. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results showed that students in the high and medium categories met the indicators for all algebraic thinking, while students in the low category did not meet the algebraic thinking indicators. At the cognitive level, S1 subject meet all cognitive levels, S2 subject do not meet the cognitive level of knowledge utilization, and S3 subject only meet the cognitive analysis knowledge level.